The enigma of Balint's syndrome: complexity of neural substrates and cognitive deficits - Magdalena Chechlacz (Frontiers Research Topics, 2015)
Bálint's syndrome is named after the Hungarian physician who first reported a remarkable case of a man with complex visuospatial deficits following bilateral lesions within parietal and occipital cortex (Bálint, 1909). The syndrome has three primary symptoms: simultanagnosia (impaired spatial awareness of more than one object at time), optic ataxia (misreaching to visual targets) and ocular apraxia (described by Bálint as "psychic paralysis of gaze"). Balint's patients not only cannot perceive more than one object at time and therefore show poor comprehension of multi-object visual scenes i.e. poor detection of all the objects present and difficulty in grasping the relationship between them; in addition they typically fail to reach towards location of the single object, which they can perceive. The deficit of the allocation of spatial attention in Balint's syndrome has been linked to a problem in feature binding which results in illusory conjunctions. Patients with Balint's syndrome also show deficits in global processing i.e. when integration of multiple local elements into global compound shapes is required. Consequently, Balint's syndrome provides a unique opportunity to study the nature and neuroanatomy of human visuospatial processing, in particular multi-level object representation, spatial awareness and the distribution of visual attention. The studies collected here cover both the anatomical and the cognitive mechanisms of the different symptoms associated with the syndrome. Furthermore, the dissociations between the components of Bálints' syndrome, in particular simultanagnosia and optic ataxia, can also co-occur with visual neglect and extinction and the different combinations of reported lesions raises a question about the status of the syndrome and whether it should be merely treated as a historical compilation of symptoms which may or may not coexist cohesively. This interesting argument is raised here.